2013
DOI: 10.1002/bdra.23162
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid fortification and the birth prevalence of congenital heart defect cases in Alberta, Canada

Abstract: FAF alone does not have an impact on the prevalence of CHDs as a group and the majority of selected types of CHDs in Alberta. The decrease in LVOTO, particularly coarctation of the aorta, may be due to FAF or other environmental factors. The increase in ASD and ASD with ventricular septal defect may reflect an increase in diagnosis and ascertainment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…These different CHD subgroups included conotruncal defects (common truncus, transposition of the great vessels, Tetralogy of Fallot), severe nonconotruncal defects (including endocardial cushion defects, common ventricle, and hypoplastic left heart syndrome), coarctation of the aorta, VSDs, ASDs, and "other heart and circulatory system abnormalities" (all ICD codes for congenital heart defects not included in the first 5 categories). Separate analysis of trends in prevalence for each one of these CHD subgroups comprised of anatomically similar specific CHD phenotypes allowed for a more robust assessment of trends in prevalence pre and post FAFF and to corroborate expected changes in prevalence for CHD subgroups previously reported to show associations with folic acid intake, namely conotruncal defects and VSDs (13)(14)(15)17,20,21,23). Of interest is that the decreasing trends in prevalence for these two subgroups of CHD continued well beyond the implementation of the FAFF policy, suggesting that other factors besides FAFF may have contributed in part to the decrease in prevalence during this period.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…These different CHD subgroups included conotruncal defects (common truncus, transposition of the great vessels, Tetralogy of Fallot), severe nonconotruncal defects (including endocardial cushion defects, common ventricle, and hypoplastic left heart syndrome), coarctation of the aorta, VSDs, ASDs, and "other heart and circulatory system abnormalities" (all ICD codes for congenital heart defects not included in the first 5 categories). Separate analysis of trends in prevalence for each one of these CHD subgroups comprised of anatomically similar specific CHD phenotypes allowed for a more robust assessment of trends in prevalence pre and post FAFF and to corroborate expected changes in prevalence for CHD subgroups previously reported to show associations with folic acid intake, namely conotruncal defects and VSDs (13)(14)(15)17,20,21,23). Of interest is that the decreasing trends in prevalence for these two subgroups of CHD continued well beyond the implementation of the FAFF policy, suggesting that other factors besides FAFF may have contributed in part to the decrease in prevalence during this period.…”
Section: Introductionmentioning
confidence: 55%
“…As pointed out in the study by Liu and colleagues (24), there are several studies in the literature supporting a preventative role for folic acid in the development of CHDs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)24). These studies were reviewed and the findings demonstrated a similar trend in relation to the inverse association of outflow tract anomalies (most consistently conotruncal defects) and ventricular septal defects with the supplementation of either isolated folic acid (by dietary fortification or pharmaceutical supplementation) or multivitamin supplementation.…”
Section: Challenges In Drawing Causal Inferences From Ecologic Analysmentioning
confidence: 86%
See 2 more Smart Citations
“…Ionescu-Ittu et al showed that the risk of severe CHD (tetralogy of Fallot, endocardial cushion defects, univentricular hearts, truncus arteriosus, or transposition complexes) in Quebec administrative databases declined by approximately 6% in the years following FA fortification in 1998 in Canada (i.e., analyzing birth data between 1990 and 2005) [29]. In contrast, a recent study in Alberta showed that only the prevalence of cases with left ventricular outflow tract obstruction declined after fortification when comparing birth data between 1995 and 1997 and between 1999 and 2002 [30]. A further case-control study on fetuses and infants with conotruncal or limb defects in a Californian birth cohort from 1987 to 1988 showed that consuming FA-containing supplements reduces the risk for conotruncal heart defects [odds ratio 0.53 (0.34-0.85)] [31].…”
Section: Timely Supplementation Of Folate Prevents Birth Defectsmentioning
confidence: 99%